TECHNOLOGICAL INNOVATION IN INTEGRATION AND INTERCONNECTION OF SCIENCE IN ISLAMIC HIGHER EDUCATION - Muh Syauqi Malik (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2020)
Technological progress cannot be hindered because today, education is entering the industrial era 4.0 characterized by education that uses digital technology in the learning process. With the use of this technology, the learning process is not limited to space and time. The terms religious knowledge and general science should not exist. Science is one unit because its source is from the Koran. This study aims to explain technological innovation in the integration and interconnection of science in Islamic higher education. This research is a research library. Therefore, what is done is exploring several data by examining in-depth reference sources from national and international journal articles and reading books relevant to the research. The data collection method that researchers use is by collecting books, articles, journals, and opinions which reveal and study the Interconnection Integration. The study results indicate that the integration and interconnection of knowledge can be achieved if learning refers to the principles of integration between Hadarah an-Nash, Hadarah al-Ilm, and Hadarah al-Falsafah. Technological advances can be used to achieve these goals, such as e-learning, digital learning resources, and teleconferencing.